The Importance of Representing the Physical Universe or Virtual Universes in Functional State Space to the Progress of Physics - Williams, Andy (My University, 2022)
Human-Centric Functional Modeling is a newly emerging branch of network theory that is hypothesized to define a methodology for representing any system, including the physical universe or any object in it. This paper explores how any region in the physical universe or how any virtual representation of such a region might be represented this way, as well as outlining the benefits of doing so.
Keywords: General Collective Intelligence; philosophy of science; state space